Estimating utility-consistent poverty lines - Arndt, Channing; Simler, Kenneth R. (International Food Policy Research Institute, 2005)
The “Cost of Basic Needs” (CBN) approach to drawing consumption-based poverty lines is widely applied and lays credible claim to being the best practice for estimating poverty measures. Unfortunately, a growing mass of evidence indicates that poverty estimates obtained under the CBN approach are often demonstrably utility inconsistent. Here, we introduce an information theoretic approach for estimating utility-consistent poverty lines. An example of the approach is provided for the case of Mozambique. The approach represents a powerful addition to the poverty analyst’s tool kit and enhances the attractiveness of the CBN approach for practical poverty measurement problems.